2013
DOI: 10.1371/journal.pone.0063782
|View full text |Cite
|
Sign up to set email alerts
|

Novel Animal Defenses against Predation: A Snail Egg Neurotoxin Combining Lectin and Pore-Forming Chains That Resembles Plant Defense and Bacteria Attack Toxins

Abstract: Although most eggs are intensely predated, the aerial egg clutches from the aquatic snail Pomacea canaliculata have only one reported predator due to unparalleled biochemical defenses. These include two storage-proteins: ovorubin that provides a conspicuous (presumably warning) coloration and has antinutritive and antidigestive properties, and PcPV2 a neurotoxin with lethal effect on rodents. We sequenced PcPV2 and studied whether it was able to withstand the gastrointestinal environment and reach circulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
1
33

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(128 citation statements)
references
References 51 publications
7
87
1
33
Order By: Relevance
“…A functional study performed after its ingestion by rats showed that PcPV2 has the ability to withstand protease digestion, displaying structural stability within the pH range of the gastrointestinal tract of rats. Moreover, this toxic lectin binds to the glycocalyx of rat enterocytes in vivo and to Caco-2 cells in culture [8]. This interaction is also in agreement with the high cytotoxic effect of the snail PVF on Caco-2 cells observed in this study.…”
Section: Discussionsupporting
confidence: 91%
“…A functional study performed after its ingestion by rats showed that PcPV2 has the ability to withstand protease digestion, displaying structural stability within the pH range of the gastrointestinal tract of rats. Moreover, this toxic lectin binds to the glycocalyx of rat enterocytes in vivo and to Caco-2 cells in culture [8]. This interaction is also in agreement with the high cytotoxic effect of the snail PVF on Caco-2 cells observed in this study.…”
Section: Discussionsupporting
confidence: 91%
“…We focused the analysis on Group B homologs, which comprised the subclade B of seven genes with high expression in the albumen gland and their coding proteins detected in the PVF. Remarkably, the two PV2 subunits of P. canaliculata which exert neurotoxicity to mice 14,15 were not detected in P. diffusa PVF ( Figure S3, supporting information). 42 Studies of venom proteins showed that positive selection sites might be adaptive to predation and defense because most of the adaptive sites are located on the functional domains.…”
Section: Resultsmentioning
confidence: 96%
“…Remarkably, the two PV2 subunits of P. canaliculata which exert neurotoxicity to mice were not detected in P. diffusa PVF (Table ). The acquisition of neurotoxic PV2 in the terrestrial eggs of Pomacea may be an important biochemical defense mechanism against terrestrial predators .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations